'Campi nomadi' as sites of resistance: The experience of Romani camp dwellers in Rome. Issue 3 (1st September 2016) - Armillei, Riccardo
ABSTRACT: This article focuses on the Romani people who live at the margins of Italian society, often in city camps that show signs of institutional abandonment, neglect and extreme decay. Every year, large amounts of public money are spent on managing these camps, whetting the appetites of various institutions, both private and public. Consequently, the Romani issue has turned into a business involving hundreds of employees in which it is very hard to know exactly how funds are actually used. However, as well as the top-down approach adopted by the Government and its agents, this study also uncovers the existence of a bottom-up opposition expressed by the Romani communities living in camps. The Romani camp dwellers have recently been described as 'fighters' or 'warriors' in the sense that they have learned to take advantage of their marginal conditions. The daily struggle to make the best of a bad situation might be interpreted as a form of resistance. Inside the camps, Romanies now occupy an in-between position, partly imposed on them by outside forces and partly the consequence of their own volition. While standing on the side of the subjugated and against a hierarchy which produces and reproduces injustice, this article examines how Romani camp dwellers have managed to exercise what remains to them of their free agency.